Family Business and Digital Transformation - Daskalopoulos, Efthymios; Machek, Ondřej, 1985-; Orel, Marko, 1986-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
Family firms are at an intertidal moment. Traditionally highly adaptable and resilient entities, defined by the family's involvement on multiple levels, family firms can either leverage their unique characteristics and transform in the digital era or fall prey to their inefficiencies. Surprisingly, even though digital transformation belongs to widely discussed themes in current management science, when it comes to investigating the phenomena of the most prevalent organisational form of businesses - family firms - the literature has been relatively silent. This dissertation provides theoretical and empirical insights into the business context of family firms competing in the current era of digital transformation and AI technologies. It comprises four interrelated articles employing a mix of methodologies: a review, a conceptual paper, and two quantitative studies. Through an analysis of the relevant peer-reviewed articles on the intersection between digital transformation and family business, the article identifies a central scholarly perspective: family businesses, often considered resource-constrained, possess unique assets and exhibit a distinctive ability to develop new capabilities which can play a significant role in navigating digital transformation and AI technologies. Building on the resource-based view, the second article conceptually develops the concept of family slack, defining the subdimensions of distinctive resources above the minimum necessary to produce a given organisational or performance output level and connecting them with possible drivers of digital transformation.
The third article is a quantitative study drawing on a large, cross-sectional dataset from an online panel study with 582 management-level participants from UK firms, exploring whether bridging and bonding social capital resources significantly promote digital transformation by indirectly developing an ambidextrous orientation, the ability to balance exploration and exploitation. The study connects the stream of digital transformation research to that of family business research. The fourth article is also a quantitative study utilising a second wave of data collection with the same participants to provide longitudinal data and explore the mediating role of decision-making comprehensiveness in the relationship between AI adoption and the development of an ambidextrous capability. Testing also for possible moderating effects of family involvement, our results suggest that family firms may benefit equally from AI despite potential hesitations. Collectively, these articles offer a structured examination of a resource-based perspective on family firms in the era of digital transformation and AI, tracing its theoretical foundations and practical applications toward developing a systematic framework for digital and AI-enabled family firms.
Vedoucí práce: Ondřej Machek
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management and managerial economics [obor disert. práce]; disertace; dissertations